Mechanical Properties and Flame Retardancy of Epoxy Resin/Nanoclay/Multiwalled Carbon Nanotube Nanocomposites - Tuan Anh Nguyen; Quang Tung Nguyen; Trong Phuc Bach (Journal of Chemistry)
This paper reports the improvement of the mechanical properties and flame retardant properties of epoxy Epikote 240/nanoclay I.30E/multiwalled carbon nanotube nanocomposite prepared by mechanical stirring method combined with ultrasonic vibration, nanoclay I.30E content (1; 2; 3 wt.%) and content of MWNT (0.01; 0.02; 0.03 wt.%). When burned, MWCNT reduces degradation speed of epoxy Epikote 240 resin and increases the char yield, and nanoclay acts as an energy storage medium to hinder the heat transfer in epoxy resin. The limiting oxygen index value and UL94 test indicated improvement of flame retardancy of the nanocomposites. The results exhibit the potentiality of these based epoxy Epikote 240 resin/nanoclay I.30E/MWCNTs nanocomposites for multifaceted advanced applications. These fillers can produce environmental friendly products with high thermal and mechanical properties.